Strategi Strategies to Increase Public Awareness of the Importance of Halal Food Certifcation for MSMES: A Case Studi of the Kebagusan Village Community - Muhtazam, Fadhli; Adinugraha, Hendri Hermawan (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
This research aims to find out effective strategies in increasing the awareness of the Kebagusan Village community about the importance of halal food certification for MSMEs. This research is a case study with a qualitative approach. The data sources used in this research come from interviews and various literature journal articles relevant to the research topic. The data analysis method used is thematic analysis. Halal food certification is the most important thing in the food industry, especially for Micro, Small and Medium Enterprises (MSMEs). The knowledge of the people of Kebagusan Village regarding halal certification is generally still limited, where halal certification is understood as a process of examining raw materials, production processes, and product quality control systems to ensure halalness according to established standards, but many only know the extent of getting a halal logo without understanding its broader benefits. The main factor hindering MSMEs in this village from pursuing halal certification is a lack of knowledge and socialization, with many businesses not fully understanding the procedures and benefits and seeing it as a formality. Minimal socialization, especially through social media which is less accessible to older MSME players, is also an obstacle. Therefore, strategies to increase awareness of halal certification including socialization, counseling and education are very important.